Jackson People’s School: Student-Centered Pedagogy as a Planning Initiative - Ponder, Sage; Wright, Willie Jamaal; Jacobs, Fayola; Didla, Noel; Wilkerson, Theron; Bakari, Akil (ACME, 2025)
In August of 2017 an audit of Jackson Public Schools (JPS) conducted by the Mississippi Department of Education listed the school district as in a state of “extreme emergency.” This emergency also coincided with other local infrastructural emergencies. Consistent with its historical disposition towards the majority-Black capital city, the Republican-dominated Mississippi State Legislature proposed an austerity measure that would result in the state’s takeover of the city’s public school system. This measure would have removed the rights of JPS and parents to determine how their children would be educated, supplanting their agency with that of an often-hostile State administrative body. JPS staved off the takeover, in part, via a partnership with the Kellogg Foundation. Desiring to supplement the city’s public-private partnership with a student-centered approach to education, and in coordination with the Lumumba Mayoral administration’s method of governing through community consensus, the authors initiated the Jackson People’s School in early 2020. Modeled after the Freedom Schools of the Civil Rights Movement, Jackson People’s School was a collective reading group designed to provide political education to teenage Jacksonians. Positioning the project as a radical planning initiative, we discuss the origins, pedagogy and successes and challenges of launching the Jackson People’s Schools project immediately prior to the onset of a global pandemic in order to illustrate how politically oppressed groups build the skills to engage in radical planning practices in restrictive political environments.